Gaza Students at RMU; Bridging Education Beyond Borders - Umar, Muhammad; Khan, Jahangir Sarwar; Mughal, Arsalan Manzoor; Riaz, Mehwish (Journal of Rawalpindi Medical College, 2025)
The academic year 2024–2025 has been an important and moving chapter for Rawalpindi Medical University (RMU). During this period RMU had the privilege to host 38 medical students from Al-Azhar University, Gaza, whose campus and homes were destroyed in the war. This initiative was provided by RMU on voluntary and humanitarian grounds to help students who had lost their institutions, families, and in some cases parents. Our purpose was to give them safe continuity of education, and the professional training required to become physicians. The Government of Punjab and Pakistan Medical & Dental Council played a vital role in registration and facilitation of these students. The arrival of these students strengthened our academic community. Their determination and personal stories of loss and resilience created learning opportunities beyond the formal curriculum. They joined RMU not only as learners but also as members of our academic family. From the first day we sought to provide a secure, welcoming, and academically stimulating environment that acknowledged both their educational needs and their personal hardships. A hybrid curriculum was designed in collaboration with Al Azhar University, Gaza specifically for these students. The academic session formally began with a welcome ceremony held on 30 October 2024 at the New Teaching Block. At that event the students were introduced to faculty, department heads and peers. This marked the formal start of the year and prepared the ground for teaching, clinical placements and collegial interaction. Following the ceremony an orientation programme was conducted in which deans of all departments presented their departments and expectations. At the outset the students underwent baseline academic, physical and psychological assessment so that bespoke support plans could be made. A foundation week was organised to address gaps in basic sciences and to align prior learning with RMU’s curriculum. In addition to formal teaching we focused on students’ well-being and social integration. RMU organised a night gala that combined sports, cultural activities and community celebration. The university dedicated the newly renovated Sports Complex to these students; the complex had been refurbished with donations and was formally inaugurated by one of the Gaza students. Over the twelve months the Gaza students participated actively in clinical rotations across multiple specialties. These attachments provided supervised, hands-on experience and helped refine clinical reasoning, procedural skills and professional conduct. Faculty members offered regular feedback and targeted mentoring to help each student meet learning objectives. Continuous evaluation was used to monitor progress and to tailor remediation where needed. The academic year also emphasised peer support and community engagement. RMU students, staff and the visiting group took part in joint academic sessions, journal clubs and community outreach activities. These interactions fostered intercultural understanding and helped the Gaza students rebuild academic networks that are essential for their future careers. As the academic year comes to an end, we warmly celebrate the students’ hard work and progress. Their perseverance and steady academic improvement have shown, in a simple and clear way, how education can heal pain and bring people closer. RMU will continue to support them until they complete their training and return home as licensed doctors prepared to serve their communities. In short, the year 2024–2025 reminded us that medical education is more than teaching facts. It is also a duty of care and solidarity. When institutions act with compassion and responsibility they help keep learning alive for those affected by conflict and displacement. For RMU this is a moral obligation, and we are determined to continue this support in the coming years.